Assessment of Healthcare Professionals' Self-Perceived Competence in Perinatal/Neonatal Palliative Care After a 3-Day Training Course - Hammond, Jennifer; Wool, Charlotte; Parravicini, Elvira (Frontiers in Pediatrics, 2020)
Background Perinatal/neonatal palliative care (PNPC) offers a plan of care for improving the quality of life of infants when the prolongation of life is no longer the goal of care. The number of PNPC programs has increased in recent years, but training for clinicians has not kept pace. Therefore, an interdisciplinary team developed a three-day intensive PNPC training course for physicians, nurses, and other healthcare professionals at Columbia University Irving Medical Center (CUIMC). Objective The aim of this study was to assess the efficacy of a PNPC training course in improving the self-reported competence of participants. Study Design A cross-sectional survey design was used to obtain data from 88 healthcare professionals who attended the PNPC training course. Data was collected using a validated questionnaire. The questionnaire included 32 items that queried participants about their self-assessed competence using a forced 1 to 4 Likert scale. The 32 items, which served as the outcome variables, were clustered into the eight domains of palliative care. The survey was administered through a web-based tool at the beginning and the conclusion of the course. Results Results from two-sample t-tests comparing pre-test and post-test self-assessed competence were statistically significant for each item across disciplines. Additional analysis revealed that after participation in the training course, the statistically significant differences between physicians’ and nurses’ pre-course self-reported competence disappeared. Conclusion The development of an evidence-based curriculum improved the self-reported competence of participants across disciplines, filled a specific gap in nurses’ self-reported competence and addressed a global training need.